Strategic Innovation: Integrating System Dynamics into Management Control - Hamza, EL KEZAZY; HIJAB, Zaynab; Oumaima, EL BAKKOURI; Amal, MELLOULI; Ezzahra, ESSAHLI Fatima (Journal of Ecohumanism, 2024)
This article explores the concept of strategic innovation, with a focus on its integration with system dynamics in the field of management control. By examining the synergies between these two domains, the article proposes innovative perspectives to enhance decision-making processes and overall business management. The authors highlight the benefits of adopting a systemic approach in management control, emphasizing how it can foster a deeper understanding of complex interactions within organizations. Practical case studies illustrate how this integration can lead to significant innovations, providing managers with valuable tools to navigate in an ever-evolving business environment. Ultimately, the article underscores the strategic importance of merging systems thinking with management control to promote more effective, resilient, and future-oriented business management.